The Effectiveness of Madura Local Art-Based YouTube in Teaching Speaking - Aditya, Tera Athena; Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2017)
YouTube is one of the online media used by the people to transfer idea or information. The researcher investigated the use of YouTube which consisted of Madura local Arts in teaching speaking. The philosophy of Madura Traditional dancing were used as the materials in speaking class. The philosophy consists of two aspects, those are: the history of the dancing and the moment held the performances. These things are new for the second semester. There was one class in second semester. The researcher used true-experimental and applied simple random sampling for 66 students into two groups. The way of researcher applied that sampling technique is through students’ attendance list number (even and odd number). The odd number was formed to be a new group. The researcher decided the odd number group as control group and the rest (even number) was an experimental group by throwing the coin. They could listen and watch the videos through YouTube. And the following step was noting the speaking log as the instrument to note what have they watched, made summary and retell. After getting treatment for 3 weeks, the posttest has been analyzed by using SPSS showed that was Ho has been rejected and H1 was accepted. In other words, there was positive effect from using YouTube which consisted of Madura Local Art toward the students’ speaking skill. After conducting pre and posttest, it shown that Madura Local art-Based YouTube was effective to build the students’ speaking skill and it is recommend for further researchers to attempt other Traditional Local Art-Based YouTube